Physical-chemical characterization of historical Portuguese tiles - Morais Pereira, S. (2012)
A group of Portuguese tiles from the 17th century with manufacturing defects and several forms of decay were characterized as to chemical and mineralogical composition and physical properties of the glaze and ceramic body. The study included multi-analytical techniques: X-ray fluorescence (XRF), X-ray diffraction (XRD) and thermogravimetric and differential thermal analysis. The porous structure of the tiles and water behavior were studied by mercury intrusion porosimetry, specific surface analysis by the method of nitrogen adsorption – BET. Water imbibition tests and hydrostatic weighing completed the characterization of the porous system. Thermal expansion and water dilation were studied through dilatometry measurements. The results of the characterization were tentatively correlated with the susceptibility to factors that cause decay.